Transcutaneous Auricular Vagus Nerve Stimulation (tAVNS) Delivered During Upper Limb Interactive Robotic Training Demonstrates Novel Antagonist Control for Reaching Movements Following Stroke - Chang, Johanna L.; Coggins, Ashley N.; Saul, Maira; Paget-Blanc, Alexandra; Straka, Malgorzata; Wright, Jason; Datta-Chaudhuri, Timir; Zanos, Stavros; Volpe, Bruce T. (Frontiers in Neuroscience, 2021)
Implanted vagus nerve stimulation (VNS) delivered concurrently with upper limb rehabilitation has been shown to improve arm function after stroke. Transcutaneous auricular VNS (taVNS) offers a non-invasive alternative to implanted VNS and may provide similar therapeutic benefit. There is much discussion about the optimal approach for combining VNS and physical therapy, as such we sought to determine whether taVNS administered during robotic training, specifically delivered during the premotor planning stage for arm extension movements, would confer additional motor improvement in patients with chronic stroke. Thirty-six patients with chronic, moderate-severe upper limb hemiparesis (>6 months; mean Upper Extremity Fugl-Meyer score= 25  2, range 13-48), were randomized to receive 9 sessions (1 hour in length, 3x/week for 3 weeks) of active (N=18) or sham (N=18) taVNS (500 ms bursts, frequency 30Hz, pulse width 0.3 ms, max intensity 5 mA, ~250 stimulated movements per session) delivered during robotic training. taVNS was triggered by the onset of a visual cue prior to center-out arm extension movements. Clinical assessments and surface electromyography (sEMG) measures of the biceps and triceps brachii were collected during separate test sessions. Significant motor improvements were measured for both the active and sham taVNS groups, and these improvements were robust at 3 month follow-up. Compared to the sham group, the active taVNS group showed a significant reduction in spasticity of the wrist and hand at discharge (Modified Tardieu Scale; taVNS= -8.94% vs. sham= +2.97%, p< 0.05). The EMG results also demonstrated significantly increased variance for the bicep peak sEMG amplitude during extension for the active taVNS group compared to the sham group at discharge (active= 26.29% MVC ± 3.89, sham= 10.63% MVC ± 3.10, mean absolute change admission to discharge, p< 0.01), and at 3-month follow-up, the bicep peak sEMG amplitude was significantly reduced in the active taVNS group (P< 0.05). Thus, robot training improved the motor capacity of both groups, and taVNS, decreased spasticity. taVNS administered during premotor planning of movement may play a role in improving coordinated activation of the agonist-antagonist upper arm muscle groups by mitigating spasticity and increasing motor control following stroke.